Qualitative analysis of stakeholder risk perceptions in Kazakhstan's energy transformation - Zhakiyev, Nurkhat; Khamzina, Ayagoz; Bakdolotov, Aidyn; De Miglio, Rocco (Frontiers in Sustainability, 2026)
IntroductionKazakhstan's pledge to achieve carbon neutrality by 2060 confronts a legacy of coal and oil dependence and the intertwined technical, economic, and social risks of a rapid energy transition. Because implementation will hinge on stakeholder cooperation, understanding how different actors perceive these risks is essential.MethodsWe conducted a two-round Policy Delphi with stakeholders, including government officials, managers from national companies, financiers/investors, experts, and civil society representatives. Responses were organized using a four-quadrant risk framework that distinguishes implementation from consequential risks and transition risks from physical climate risks.ResultsAll risks raised by participants could be located within this framework, indicating that it captures the main concerns in the Kazakhstani context. Implementation-transition risks dominated, led by regulatory volatility, financing constraints, grid bottlenecks, fossil-fuel lobbying, and skills shortages. These risks were consistently rated as highly important across stakeholder groups, although financiers and civil society actors were less concerned about policy instability than government officials and experts.DiscussionBy clarifying where stakeholders perceive the greatest implementation risks, the study provides a practical risk map to prioritize reforms in regulation, finance, grid development, and skills, and adds a stakeholder-based perspective to research and policy debates on energy transitions in fossil-fuel-dependent economies such as Kazakhstan.